2012
DOI: 10.2176/nmc.52.194
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Immunotherapy With Combined Autologous Tumor Cell and Endothelial Cell Vaccine In Vivo

Abstract: Combined vaccines containing GL261 murine glioma cells and F-2 murine endothelial cells fixed with glutaraldehyde-phosphate buffered saline were injected into the intradermal tissue of the tail base of C57BL/6 mice. After the vaccination, GL261 cells were injected subcutaneously into the left flank of the mice. Vaccination with fixed F-2 cells induced the development of relatively high amounts of interferon-gamma-releasing cells after in vitro re-stimulation with vascular endothelial growth factor-receptor 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In addition, an interesting in vivo study assessed the effect of a combined vaccine, prepared from GBM and endothelial cells, on glioma-bearing mice. While tumor growth inhibition was seen only in the preventive use of the combined vaccine, a significantly decrease in vessel account was verified in the tumor upon the therapeutic experiment with that vaccine [37].…”
Section: Human Umbilical Vein Endothelial Cell (Huvec) Vaccinesmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, an interesting in vivo study assessed the effect of a combined vaccine, prepared from GBM and endothelial cells, on glioma-bearing mice. While tumor growth inhibition was seen only in the preventive use of the combined vaccine, a significantly decrease in vessel account was verified in the tumor upon the therapeutic experiment with that vaccine [37].…”
Section: Human Umbilical Vein Endothelial Cell (Huvec) Vaccinesmentioning
confidence: 96%
“…Interestingly, an immunotherapy strategy combining cellular vaccines (prepared from autologous GL261 murine glioma cells and F-2 murine endothelial cells) was tested on glioma-bearing mice. Such preclinical study revealed that combined vaccine significantly decreased tumor growth and vessel account, thus representing an expecting strategy capable to target both GBM cells and their microenvironment [37].…”
Section: Autologous Formalin-fixed Tumor Vaccines (Aftvs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture GL261 (mouse glioblastoma) was kindly provided from Dr. Shingo Takano (Department of Neurosurgery, Faculty of Medicine, University of Tsukuba, Tsukuba, Ibaraki, Japan) without further authentication (18). LLC was purchased from RIKEN Cell Bank.…”
Section: Micementioning
confidence: 99%
“…Finally, we tested the effect of LPA in a xenograft model using primary human GMB cells (GDC40; ref. 18). We transplanted 2 Â 10 5 GDC40 cells into brains of NOD/SCID mice.…”
Section: Lpa Promotes Fine Vascular Formation In Brain Tumorsmentioning
confidence: 99%